The Circular Plastics Economy in Mozambique : Challenges and Opportunities - World Bank (Washington, DC, 2022)
The World Bank Group developed the Mozambique problue program (MozAzul) to provide comprehensive technical assistance to the Government of Mozambique on the blue economy agenda. The objective of the MozAzul program is to strengthen the knowledge base on the sustainable blue economy development in Mozambique, and under pillar 2, specifically on marine litter. This study is intended to inform the government’s upcoming national action plan to combat marine litter as well as intensify engagement with stakeholders, including innovators and around new business models. It is mainly concerned with assessing the circular economy opportunities in Mozambique as they relate to marine plastics litter. The assignment forming the basis of this study has set its parameters on the upstream (pre-waste) opportunities for plastics circularity, leveraging the Ellen MacArthur Foundation’s ReSOLVE framework to map out the various levers that organizations may employ in their transition towards improved material efficiency. The methodology leverages extensive desk research, the collection of primary data through interviews with relevant stakeholders located in Mozambique, and interviews with key stakeholders who can provide insight on the circular opportunities and existing business models practiced in Mozambique. The methodology also leverages real-time findings concurrently being developed by local and international experts, and organizations conducting parallel studies (i.e. IUCN). As of the writing of this report, Coronavirus disease 2019 (COVID-19) continues to hamper Mozambique’s economy and health sectors. As a result of the ongoing pandemic, this report is decidedly both more thorough in explaining the new concepts and approaches leading to the explanation of circular economy opportunities in Mozambique, and simultaneously less reliant on local stakeholder interviews than initially intended.